Formulation And Physical Evaluation Of Lip Cream Using A Combination Of Beetroot Extract (Beta Vulgaris L.) And Strawberry Fruit (Fragraria Vesca L.) As Natural Colorants - Vanesa Dwi Cahyani; Annajim Daskar; Iga Mayola Pisacha; Wina Safutri (Journal of Innovative and Creativity, 2025)
The use of cosmetics, including lip cream, has become an essential part of people's lives, especially in Indonesia, as a means to enhance appearance, maintain cleanliness, and provide protection for the body. The study purpose was: : To determine the formulation of a lip cream formulation combining beetroot extract (Beta vulgaris L.) and strawberry fruit (Fragaria vesca L.) as natural colorants in lipsticks available in the Metro regional market using an experimental method. Materials and methods. Quantitative analysis was conducted through pH testing, physical evaluation of the lip cream formulation, and hedonic testing. Results: Out of ten panelists, Formula II scored the highest in most parameters compared to Formula I. Meanwhile, the lip cream formulation combining beetroot extract and strawberry extract can be used as a natural colorant capable of producing attractive and stable colors and is well-received organoleptically. Conclusions. It can be concluded that the best formula is Formula II with a balanced concentration of beetroot and strawberry extracts, and that the concentration in FII produces an optimal formulation in terms of sensory and physical properties. These findings are expected to serve as an initial reference for future researchers to utilize beetroot and strawberries in the formulation of other products such as eyeshadow and lipstick.